Tick innate immune responses to hematophagy and Ehrlichia infection at single-cell resolution - Adegoke, Abdulsalam; Ribeiro, Jose M. C.; Smith, Ryan C.; Karim, Shahid (Frontiers in Immunology, 2024)
Ticks rely on robust cellular and humoral immune responses to control microbial infection. However, several aspects of the tick's innate immune system remain uncharacterized, most notably that of the immune cells (called hemocytes), which are known to play a significant role in cellular and humoral responses toward microbes. Despite the importance of hemocytes in regulating microbial infection, our understanding of their basic biology and molecular mechanisms remains limited. Therefore, we believe that a more detailed understanding of the role of hemocytes in the interactions between ticks and tick-borne microbes is crucial to illuminate their function in vector competence and to help identify novel targets for developing new strategies to block tick-borne pathogen transmission. This study examined hemocytes from the lone star tick (Amblyomma americanum) at the transcriptomic level using the 10X genomics single-cell RNA sequencing platform to analyze hemocyte populations from unfed, partially blood-fed, and Ehrlichia chaffeensis-infected ticks. Our data exhibit the identification of twelve and nineteen distinct hemocyte populations, respectively, from uninfected and Ehrlichia-infected ticks. Our results show a significant increase of clusters representing granulocyte and oenocytoids populations with Ehrlichia infection. This work opens a new field of tick innate immunobiology to understand the role of hemocytes, particularly in response to prolonged blood-feeding (hematophagy) and tick-microbial interactions.